Liberalization and customer behavior in the Portuguese residential retail electricity market. (August 2019) - Fotouhi Ghazvini, Mohammad Ali; Ramos, Sergio; Soares, João; Castro, Rui; Vale, Zita
Abstract: The final step that Portugal is taking to reach a fully liberalized electricity market is the deregulation of the retail market by phasing-out regulated electricity prices and reducing the administrative burdens in this area. These attempts are done to promote the entrance of companies into the retailing business and to actively engage the end-users in the market. This analysis shows that despite high consumer switching rates during the 2013–2015 period, the retail market in Portugal is still highly concentrated. The retail rates are also not following the changes in the wholesale market price.